2017
DOI: 10.1186/s40359-017-0206-z
|View full text |Cite
|
Sign up to set email alerts
|

Memories of paternal relations are associated with coping and defense mechanisms in breast cancer patients: an observational study

Abstract: BackgroundBreast cancer diagnosis and treatment represent stressful events that demand emotional adjustment, thus recruiting coping strategies and defense mechanisms. As parental relations were shown to influence emotion regulation patterns and adaptive processes in adulthood, the present study investigated whether they are specifically associated to coping and defense mechanisms in patients with breast cancer.MethodsOne hundred and ten women hospitalized for breast cancer surgery were administered questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…According to their empirical results, a higher prevalence of displacement, regression, reaction formation, and projection of DM in patients with BC was associated with lower cognitive and role aspects of quality of life. Renzi et al (2017) had found that patients with BC with overprotective parents used more fantasy and withdrawal as DM, while patients with BC with less protective parents used more repression. They argued that repression might be beneficial for a patient to overcome BC.…”
Section: Introductionmentioning
confidence: 99%
“…According to their empirical results, a higher prevalence of displacement, regression, reaction formation, and projection of DM in patients with BC was associated with lower cognitive and role aspects of quality of life. Renzi et al (2017) had found that patients with BC with overprotective parents used more fantasy and withdrawal as DM, while patients with BC with less protective parents used more repression. They argued that repression might be beneficial for a patient to overcome BC.…”
Section: Introductionmentioning
confidence: 99%
“…30 It is important to underline that defence mechanisms are related to coping styles 31 , and some studies have shown that immature defence mechanisms are significantly associated with a dysfunctional coping style, such as impotence/despair, which determines a pessimistic attitude that hinders the therapeutic alliance, and reduces the quality of life and survival to cancer. 16 Some authors have highlighted the importance of the environmental context among the factors capable of inducing PTG, such as access to programmes of psychological and social support during treatment. 32 The patient goes beyond resilience, with the search for a higher level of functioning and the achievement of even greater well-being than the one preceding the disease.…”
Section: Main Findingsmentioning
confidence: 99%
“…15 Although some scientists continue to consider them outdated concepts, recent studies have been conducted to confirm their importance in patients with cancer. 16 In a recent meta-analysis 17 , a correlation was observed between the defence mechanism of repression and worse physical and emotional health-related quality of life, and the defences of action predicted fewer chances of survival. Further investigations of these mechanisms seem to be fundamental to understand how to manage the psychological recovery of patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attachment theory has been extended in its conceptual territories to include psychopathology, affect regulation, interpersonal relationships and stress responses in adulthood as well as childhood [ 15 , 16 ]. Pioneering attempts have been made to establish attachment theory as a conceptual frame in which to identify the psychological aspects of cancer [ 12 - 14 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this way, a patient’s attachment system may be re-activated and displayed with emotional difficulty (distress) when diagnosed or treated for BC. There have been limited studies of attachment security issues in the BC population from the perspectives of quality of life [ 19 , 21 ], coping strategies [ 17 , 19 ], rapport or relationship with the surgeon and the patient’s family [ 22 , 23 ], immune response [ 24 ], and screening behavior [ 25 ]. However, little research has addressed the relationship of attachment insecurity with psychological distress.…”
Section: Introductionmentioning
confidence: 99%